Śrīmadbhāgavatāntargata Nrsiṃhākhyāna, arthāt, Pralhadacaritra [i.e. Prāhlādacaritra] : Nārāyaṇakavaca, Lakṣmīnrsiṃhastotra, Bhāgavatasaptāhavidhi āṇi Bhāgavata va Lakṣmīnrsiṃha yāñci āratī yāṁsaha (Induprakāśa Chāpākhānyānta, 1927)
On the episode of Nrsiṃha (Hindu deity) and Prahlāda; portion of Hindu mythological text; includes prayers for various deities.